Local habitat use by botos (Amazon river dolphins, Inia geoffrensis) using passive acoustic methods. Issue 1 (20th July 2015) - Yamamoto, Yukiko; Akamatsu, Tomonari; da Silva, Vera M. F.; Kohshima, Shiro
Abstract: We monitored the underwater behavior of botos ( Inia geoffrensis ) using stereo acoustic data loggers to observe their local habitat use and its diel changes at the Mamirauá Sustainable Development Reserve, Brazil. A‐tags were set at five sites in three different habitat types: Lake (low current), Channel (middle current), and Junction (junction of two channels). The presence index during nighttime was significantly greater than during daytime in the Lake and Junction. Underwater movement was estimated from the changing pattern (trajectory) of the relative angle of the sound source from A‐tags. A staying‐type trajectory was dominant in the Lake, although the prevalence of moving‐type trajectory increased at night. More than 80% of detected trajectories were the staying type in the Junction, while moving‐type trajectories dominated in the Channel. The frequency of click trains was greatest in the Lake, followed by the Junction and Channels. The average interpulse interval, which reflects the mean target distance of echolocation, was shortest in the Lake, followed by the Junction and Channel. These results suggest that the botos used the Lake as their primary habitat for active behaviors like foraging, especially at night, and the Junction as their primary habitat for relatively inactive behaviors at night.